Mobile communication technologies and ontological security - Amigo, Bernardo; Osorio, Francisco; Bravo, María Cecilia (Convergencia Revista de Ciencias Sociales, 2017)
This paper analyzes the relationship between everyday life and the mass use of mobile communication technologies, especially smartphones. From a methodological point of view, qualitative research was used in order to grasp the meanings people give to the use of such technologies. Data were gathered through 24 focus groups and 20 in-depth interviews with youths aged between 16 and 25 years of age in Santiago de Chile between 2014 and 2015. Results show that the people’s uses of mobile communication systems would be creating changes in the daily experience of time and space, and in the way in which they give stability, structure and meaning to the intersubjective world. The article concludes that the concept of ubiquitous everyday life, or hyper everyday life, may explain the meaning of the current transformations.
Keywords: everyday life; time; space; mobile phone; ontological security.